2015
DOI: 10.1080/15475778.2015.1093784
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Institutional Distance and MNEs’ Host Country Experience on the Ownership Strategy in Cross-Border M&As in Emerging Economies

Abstract: ABTRACT:This paper analyzes ownership strategy in cross-border mergers and acquisitions (CB M&As) undertaken by the multinational enterprises (MNEs) in emerging economies. We use new institutional economics and organizational learning theories to hypothesize and empirically analyze the influence of formal and informal institutional distance, and MNEs' host country experience on the MNEs' choice between full and partial CB M&As. The empirical analysis is based on a sample of 184 CB M&As launched by MNEs in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 86 publications
(79 reference statements)
3
30
0
Order By: Relevance
“…Ando (2012) shows that the effect of formal institutional distance on the percentage of equity sought is reduced for firms with greater international experience, and also for firms with combined greater international experience and host-country experience. Likewise, Arslan and Dikova (2015) also confirm that the effect of formal institutional distance on the percentage of equity sought is weaker for firms with greater host-country experience.…”
Section: Heterogeneous Responses To Institutional Uncertaintysupporting
confidence: 56%
See 1 more Smart Citation
“…Ando (2012) shows that the effect of formal institutional distance on the percentage of equity sought is reduced for firms with greater international experience, and also for firms with combined greater international experience and host-country experience. Likewise, Arslan and Dikova (2015) also confirm that the effect of formal institutional distance on the percentage of equity sought is weaker for firms with greater host-country experience.…”
Section: Heterogeneous Responses To Institutional Uncertaintysupporting
confidence: 56%
“…Accordingly, evidence shows that acquirers tend to opt for lower equity share in their cross-border targets when host country risk is higher (Chari and Chang, 2009). While the direct effect of institutional risk or uncertainty on the entry mode choice has been extensively investigated (Brouthers and Hennart, 2007), there are relatively fewer studies on moderating factors affecting this relationship (Ando, 2012;Arslan and Dikova, 2015;Cui and Jiang, 2012;Liou et al, 2017). The studies available show that diverse factors come into play, such as acquirer's international experience (Ando, 2012), acquirer's host country experience (Arslan and Dikova, 2015), state ownership of acquirer (Cui and Jiang, 2012), and even the stage of development of home country human resources (Liou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Institutional distance refers to differences in both formal and informal institutions of home and host countries of entering firms (e.g., Estrin et al, 2009;Arslan and Dikova, 2015).…”
Section: Informal Institutional Distancementioning
confidence: 99%
“…Literature has shown that these cognitive aspects of institutional differences tend to influence a range of subsidiary management issues for internationalising foreign firms. Some of these issues include understanding the desires of local employees, transfer and management of organisational knowledge to the subsidiary, and the degree of adaptation required for operational strategies (e.g., Michailova and Hutchings, 2006;Chang et al, 2012;Arslan and Dikova, 2015).…”
Section: Informal Institutional Distancementioning
confidence: 99%
See 1 more Smart Citation